The Megafauna3D Dataset: 3D Models of Late Pleistocene Megafauna Fossils From Uruguay - Luciano Varela; P. Sebastián Tambusso; Martín Batallés; Gabriela Costoya; Richard A. Fariña (Journal of Open Archaeology Data)
This dataset consists of 3D digital models of fossilised remains from the Pleistocene megafauna of Uruguay, now publicly available for scientists, educators, and the general public. The fossils, housed in collections across Uruguay, were digitised through photogrammetry, structured light, and CT scanning. The dataset includes models of extinct species such as ground sloths, glyptodonts, mastodonts, and a sabre-toothed cat, which played significant roles in the Pleistocene ecosystems. The dataset is stored in the MorphoSource repository under an open licence, allowing for broad reuse in research, education, and public outreach.